H. pylori isolates with amino acid sequence polymorphisms as presence of both HtrA-L171 & CagL-Y58/E59 increase the risk of gastric cancer - Yeh, Yi-Chun; Kuo, Hsin-Yu; Chang, Wei-Lun; Yang, Hsiao-Bai; Lu, Cheng-Chan; Cheng, Hsiu-Chi; Wu, Ming-Shiang; Sheu, Bor-Shyang (Journal of biomedical science, 2019)
Background H. pylori CagL-Y58/E59 increase gastric cancer risk by stronger binding with integrin to faciliate type IV secretory system (T4SS). H. pylori can secrete high temperature requirement A (HtrA) to mediate E-Cadherin cleavage for gastric epithelial junction disruption, so H. pylori CagL can adhere to integrin located on basolateral side of epithelium. The study test whether H. pylori HtrA amino acid polymorphisms can increase gastric cancer risk synergistically with CagL-Y58/E59. Methods One-hundred and sixty-four H. pylori -positive patients, including 71 with non-ulcer dyspepsia (NUD), 63 with peptic ulcers (PU), and 30 with gastric cancers (GC), were enrolled to receive upper gastrointestinal endoscopy to obtain gastric biopsies for H. pylori culture and histology by the updated Sydney system. Each isolate was screened for htrA & cagL genotype by polymerase chain reaction and HtrA & CagL-Y58/E59 amino acid sequence polymorphisms by sequencing. Results The prevalence rates of htrA & cagL gene were both 100%. The HtrA amino acid sequence polymorphisms were not different between NUD and PU. The H. pylori isolates of GC had higher rates of HtrA residue 171 as leucine than those of NUD (73.3% vs. 50.7%, P = 0.036, OR[95%CI] = 2.7[1.1–6.8]). The risk of the H. pylori -infected subjects to get gastric cancer was increased up to 15.4-fold, if the infected isolates had presence of both HtrA-L171 and CagL-Y58/E59 ( P < 0.001). Conclusions The H. pylori isolates of gastric cancer subjects had a higher rate of HtrA-L171. H. pylori isolates with presence of both HtrA-171 & CagL-Y58/E59 can synergistically increase the risk of gastric cancer.